Jane Tolmach remarks from a Labor Day picnic - Jane Tolmach::::::
This document contains the text of Jane Tolmach's remarks at a Labor Day picnic, emphasizing tax reform and property tax relief as her top legislative priority. She criticizes the state's practice of shifting costs onto local property taxpayers and argues that rising assessments have made the property tax system inequitable, even forcing some homeowners out of their homes. Tolmach pledges to fight in Sacramento for comprehensive tax reform and meaningful relief for middle-income homeowners. She concludes by pointing to her record as a school trustee, mayor, and city council member as evidence of her effectiveness and commitment to representing Ventura County's interests.